2017
DOI: 10.18632/oncotarget.19969
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin in cell adhesion and migration via N-glycosylation

Abstract: Directed cell migration is an important step in effective wound healing and requires the dynamic control of the formation of cell-extracellular matrix interactions. Plasma fibronectin is an extracellular matrix glycoprotein present in blood plasma that plays crucial roles in modulating cellular adhesion and migration and thereby helping to mediate all steps of wound healing. In order to seek safe sources of plasma fibronectin for its practical use in wound dressing, we isolated fibronectin from human (homo) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(84 citation statements)
references
References 50 publications
5
79
0
Order By: Relevance
“…Previous reports have shown that N-glycosylation negatively impacts platelet adhesion to VWF in the absence of collagen, 30 however, our data indicates a positive role for N-glycans in VWF adhesion to collagen, at least under non-shear conditions. Consistent with previous studies, 31 32 we found FN1-collagen binding was positively influenced by Nglycosylation, and binding by FN1 to collagen dropped more than 2-fold following PNGase F treatment. In agreement with previous studies, 33 34 we found the PPI between vitronectin (VTN) and collagen to be enhanced 2.2-fold following sialidase treatment (Fig.…”
Section: Major Platelet Adhesive Receptors and Proteins Require N-glysupporting
confidence: 92%
“…Previous reports have shown that N-glycosylation negatively impacts platelet adhesion to VWF in the absence of collagen, 30 however, our data indicates a positive role for N-glycans in VWF adhesion to collagen, at least under non-shear conditions. Consistent with previous studies, 31 32 we found FN1-collagen binding was positively influenced by Nglycosylation, and binding by FN1 to collagen dropped more than 2-fold following PNGase F treatment. In agreement with previous studies, 33 34 we found the PPI between vitronectin (VTN) and collagen to be enhanced 2.2-fold following sialidase treatment (Fig.…”
Section: Major Platelet Adhesive Receptors and Proteins Require N-glysupporting
confidence: 92%
“…In clear cell RCC, upregulation of protein glycosylation in cancer cells may be useful in diagnosis and determining disease prognosis . Furthermore, N‐glycosylation is involved in cell adhesion and is associated with reduced expression of E‐cadherin, which modulates the metastatic potential of cancer cells . We hypothesize that this pathway might contribute to cancer pathogenesis such that upregulation of PMM2 might enhance cancer cell aggressiveness by increased N‐glycosylation.…”
Section: Discussionmentioning
confidence: 98%
“…CAMs are grouped into several families, namely, immunoglobulins, cadherins, integrins, selectins and ECM proteins (Table 1). 38,39,48,[40][41][42][43][44][45][46][47] These proteins can mediate cell adhesion by heterophilic (between cells of a different type) and homophilic (between cells of a single type) interactions. CAMs have specific affinities for cell surface glycoproteins, helping the specific location of cells within the tissues and transport of biochemical information to coordinate homeostasis including signal transduction, cellular communication, and recognition.…”
Section: Cellular Recognition and Adhesion Peptidesmentioning
confidence: 99%